Caridina variabilirostris (Crustacea: Decapoda: Atyidae), a new species of freshwater shrimp from Pohnpei (Micronesia) - de Mazancourt, Valentin; Marquet, Gerard; Keith, Philippe (European Journal of Taxonomy, 2018)
Recently, the status of a new species of atyid shrimp from Pohnpei (Micronesia) was discussed in relation to C. brachydactyla De Man, 1908 and C. mertoni J. Roux, 1911. By combining morphological data with a phylogenetic analysis with closely related species, this species is here described as Caridina variabilirostris sp. nov. Notes on its ecological distribution are also provided. The new species is characterized by a highly variable rostrum and is present in rivers all over Pohnpei Island. The status of this new species is clarified and it is shown that neither C. brachydactyla De Man 1908 nor C. mertoni J. Roux, 1911 occur on Pohnpei Island.